RELIGIOUS TEACHERS' PROFESSIONALISM AS A MAIN DRIVE FOR IMPROVING THE QUALITY OF LEARNING IN SCHOOLS: A LITERATURE REVIEW AND CONTRIBUTION TO EDUCATION POLICY IN INDONESIA - Yohanes Mihit; Lorensius Amon (Jurnal Masalah Pastoral, 2026)
This article aims to examine teacher professionalism as a key factor influencing the quality of learning in Indonesian schools through a targeted literature review spanning 2018 to 2025. The study synthesizes evidence from national and international publications to map trends in policy reforms, training initiatives, certification systems, and learning outcomes. The review highlights four important dimensions of professionalism: pedagogical competence, professional growth, social competence, and personal integrity. These dimensions shape teachers' teaching effectiveness and contribute to student engagement and academic achievement. Findings indicate that policy reforms serve as the most dominant driver for professional improvement, while digital literacy training and development programs strengthen teachers' capacity to respond to contemporary learning demands. Structural barriers such as unequal access to professional development opportunities and limited digital infrastructure remain persistent issues in some regions. This study proposes strategic directions for policies, including mentoring systems, professional learning communities, and technology-enabled development, to foster continuous professional growth and improve the quality of learning across educational contexts.